Manual of Housekeeping- care and conservation of collections in historic houses. - Reynolds, Fiona; The National Trust (Wiltshire : The National Trust, 2011)
zeer uitgebreid standaardwerk over conservering van historische collecties
Adlib record nr. 530010425
first published in 2005 in the UK and USA by Butterworth-Heinemann (reprinted 2006, 2008)
Engels
boek